(untitled) (Journal of Engineering, 2024)
The study area, which consists of carbonate, is located in the unstable Mesopotamian basin on the Arabian plate, which makes it a field with high heterogeneity. It has a discrepancy in its bubble point pressure, which raises concerns about the faults or reefs that caused it. The study’s main objective is to determine how faults and reefs impact production performance and pressure behavior under a future development strategy. This goal will be achieved by completing the necessary seismic, static, and dynamic models. After re-evaluating the seismic survey data, the seismic analysis detected many irregular amplitudes of reflected events and abrupt discontinuities, indicating either a reef or a fault. The static model was built based on seismic possible results and to make them as inputs for building the reservoir model. Based on the history-matching results, faults were detected, while reefs were ruled out. The development plan was implemented for the next 20 years in four cases, and case four had the most favorable results among all the cases, with production plateauing at 140 MSTB/D and a cumulative volume equal to 1.09 MMMSTB. The reservoir pressure behavior shows a hierarchical drop in all cases, with some differences, including a sharp decline in the area of the proposed wells and the fault, which has become a compartment that prevents reservoir compensation from adjacent regions.